First‐trimester intrauterine hematoma and pregnancy complications. (31st March 2020) - Al‐Memar, M.; Vaulet, T.; Fourie, H.; Bobdiwala, S.; Farren, J.; Saso, S.; Bracewell‐Milnes, T.; Moor, B. De; Sur, S.; Stalder, C.; Bennett, P.; Timmerman, D.; et al.
ABSTRACT: Objective: To assess whether sonographic diagnosis of intrauterine hematoma (IUH) in the first trimester of pregnancy is associated with first‐trimester miscarriage and antenatal, delivery and neonatal complications. Methods: This was a prospective observational cohort study of women with an intrauterine singleton pregnancy between 5 and 14 weeks' gestation recruited at Queen Charlotte's and Chelsea Hospital, London, UK, between March 2014 and March 2016. Participants underwent serial ultrasound examinations in the first trimester, and the presence, location, size and persistence of any IUH was evaluated. First‐trimester miscarriage was defined as pregnancy loss before 14 weeks' gestation. Clinical symptoms, including pelvic pain and vaginal bleeding, were recorded at each visit using validated symptom scores. Antenatal, delivery and neonatal outcomes were obtained from hospital records. Logistic regression analysis and the chi‐square test were used to assess the association between the presence and features of IUH and the incidence of adverse pregnancy outcome. Odds ratios (OR) were first adjusted for maternal age (aOR) and then further adjusted for the presence of vaginal bleeding or pelvic pain in the first trimester. Results: Of 1003 women recruited to the study, 946 were included in the final analysis and of these, 268 (28.3%) were diagnosed with an IUH in the first trimester. The presence of IUH was associated with the incidence of preterm birth (aOR, 1.94 (95% CI, 1.07–3.52)), but no other individual or overall antenatal, delivery or neonatal complications. No association was found between the presence of IUH in the first trimester and first‐trimester miscarriage (aOR, 0.81 (95% CI, 0.44–1.50)). These findings were independent of the absolute size of the hematoma and the presence of vaginal bleeding or pelvic pain in the first trimester. When IUH was present in the first trimester, there was no association between its size, content or position in relation to the gestational sac and overall antenatal, delivery and neonatal complications. Diagnosis of a retroplacental IUH was associated with an increased risk of overall antenatal complications ( P  = 0.04). Conclusions: Our findings demonstrate that there is no association between the presence of IUH in the first trimester and first‐trimester miscarriage. However, an association with preterm birth, independently of the presence of symptoms of pelvic pain and/or vaginal bleeding, is evident. Women diagnosed with IUH in the first trimester should be counseled about their increased risk of preterm birth and possibly be offered increased surveillance during the course of their pregnancy. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.